Optimalisasi Integrasi Media Sosial Direktorat Jenderal Pemasyarakatan Sebagai Bentuk Keterbukaan Informasi Publik - Adhiatma, Pravitea Yulia; Mahmudah, Siti Muslichatul (Jurnal Pustaka Komunikasi, 2023)
Keterbukaan Informasi Public must be implemented by government agencies based on Undang-Undang Nomor 14 Tahun 2018, one of which is the Directorate General of Corrections. The Public Relations Directorate of Corrections plays a major role in maintaining the positive image of the institution, including social media integration which can reach a wide audience. This study aims to determine the optimization in the integration of social media owned by the Directorate General of Corrections as a form of Keterbukaan Informasi Publik based on the 4C concept and The Circular Model of Some for Social Communication, using a descriptive-qualitative method. Interviews were conducted with one key informant and two informants, and results found related to characteristics, stages of management, as well as obstacles and solutions in optimizing social media. Research shown that the Directorate General of Corrections makes Instagram the main media, while other social media such as Twitter, Facebook and YouTube as supporting social media for content publication. Time management planning, content themes, collaboration, interactive communication and feature utilization are also carried out to support the information provided through social media.